Complementary feeding and caregiver sleep: findings from a representative survey in Chongqing, China - Ya Shi; Ya Shi; Shengping Li; Junping Chen; Xiangying Su; Zumin Shi; Yan Zhao; Jiaxin Guo; Jiaxin Guo; Yong Zhao; Yong Zhao; Nianrong Wang (Frontiers in Nutrition, 2025)
ObjectiveSleep health and correct complementary feeding are important considerations in public health. This study aims to confirm that correct complementary feeding (CCF) practices are complex and crucial, and they can also influence the development of healthy sleep patterns in infants’ caregivers.MethodsUsing a convenience sampling method, we identified a cohort of Chongqing caregiver-infant pairs (CQ CG-Inf P). Caregivers’ sleep conditions were primarily collected through self-reports, while complementary feeding practices were gathered using the Complementary Food Guide Tool. We employed multiple regression and subgroup analysis to explore the relationship between these factors.ResultsOf the 1,230 respondent pairs, 82.6% of infants were cared for by their mothers, 22% received CCF, and 56.3% of caregivers were housewives. Multivariate logistic regression analyses, both before (Model 1) and after (Model 2) adjustment for socio-demographic characteristics and health conditions of both children and caregivers, consistently indicate that CCF is inversely associated with the establishment of longer sleep patterns among caregivers. The results of the subgroup analysis revealed that the relationship between caregivers’ CCF and long sleep patterns was not influenced by the interaction of caregivers’ basic demographic factors.ConclusionThis study showed that caregivers providing CCF may face challenges in establishing long sleep patterns. By examining diverse feeding indicators, this research advances understanding in this field. More intuitive training on complementary feeding guidelines can support caregiver sleep health and enhance parent-child interactions.